Traditional Chinese Medicine Use in the Pathophysiological Processes of Migraine - Mei-Rong Wu; Yi Ou; Rui Han; Tian-Tian Li; Ming-Yan Wei; Hong Guo; Yao-Dong Miao; Kai Wang; Han Zhang; Lin Li (World Journal of Traditional Chinese Medicine)
Migraine is a highly prevalent neurological disorder and has been the second leading cause of disability worldwide for many years. The pathophysiology of migraines is complicated, and most available medications have unpleasant side effects. Therefore, it is essential to understand the mechanism of migraine to develop potential preventive and therapeutic agents. Studies have confirmed that traditional Chinese medicine (TCM) can alleviate migraine by reducing neuroinflammation, oxidative stress, and apoptosis and regulating neurotransmitters and vascular function. Starting from the pathophysiological process of migraine, this review summarizes the mechanisms by which TCM improves neurovascular function after migraine to provide clues and a reference for the clinical application of TCM in the prevention and treatment of migraine and guide further research and development of new drugs.